CAUSE ANALYSIS OF CONTRACT AMENDMENT IN THE X DRY DAM CONSTRUCTION PROJECT IN INDONESIA - Novika Candra Fertilia; Hana Sary Ayuningtias (NAROTAMA UNIVERSITY, Indonesia, 2020)
The government is building two dams to pursue flood capacity in Jakarta, one of which is the X Dry Dam project. There were obstacles during the construction of this project, which resulted in several changes in the form of contract amendments. The purpose of this study is to determine the most influential factors that cause contract amendments and give suggestions for that factors, so the next contract amendment can be minimized and the project can run according to the costs and time that has been set. In this study, the authors use quantitative research methods by distributing questionnaires to respondents who are staff at the contractor. Secondary data used is the S curve. This research uses 4 stages of the questionnaire by using the reliability test using SPSS version 25 software and data analysis of importance index (II). From the results of this study are the X Dry Dam Project has 5 factors that most influence the occurrence of contract amendments that are land acquisition (53.33%), severe weather conditions (52.19%), society refusal of the project (48.84%), lacking design process planning (42.12%), and schedule /estimated time by the owner is too fast (40.28%).